2015
DOI: 10.1002/nau.22933
|View full text |Cite
|
Sign up to set email alerts
|

ICS teaching module: Ambulatory urodynamic monitoring

Abstract: The clinical role of AUM is still controversial. The scientific evidence on the usefulness of AUM is still limited but the ICS Urodynamics Committee recommends its use as a second line diagnostic tool when office laboratory urodynamics have failed to achieve a diagnosis. AUM has been showed to be more sensitive than laboratory urodynamics in diagnosing detrusor overactivity but the level of evidence for this measurement is not high. This manuscript summarizes the evidence and provides practice recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, DO could be of importance in terms of its effect prediction of other treatments. The ICS urodynamics committee recommends the use of ambulatory-UDS as a second line diagnostic in specific cases [25]. Our study shows that objective improvement on ambulatory-UDS is associated with the standard evaluation parameters of subjective treatment success and the more objective voiding diary parameters.…”
Section: Discussionmentioning
confidence: 51%
“…However, DO could be of importance in terms of its effect prediction of other treatments. The ICS urodynamics committee recommends the use of ambulatory-UDS as a second line diagnostic in specific cases [25]. Our study shows that objective improvement on ambulatory-UDS is associated with the standard evaluation parameters of subjective treatment success and the more objective voiding diary parameters.…”
Section: Discussionmentioning
confidence: 51%
“…The longer duration of observation has increased detection of urodynamic abnormalities such as detrusor overactivity. [5,6] However, this technique has seen limited usage in practice. Catheters may cause discomfort or become dislocated.…”
Section: Introductionmentioning
confidence: 99%
“…Last, considerable embarrassment and a lack of privacy (due to continual observation by clinicians, nurses and technicians) leads to many individuals being unable to void during UDS, which greatly limits the diagnostic information obtained from the study. Together, these shortcomings result in 19-44% of UDS being nondiagnostic 28 .…”
Section: Diagnostic Failurementioning
confidence: 99%
“…One would expect that transient symptoms in patients with intermittent claudication represent an excellent example of a time during which a short office study might be negative whereas a longer physiological study could identify pathology. In patients with nondiagnostic conventional UDS, one study reported that AUM improved the detection of OAB compared with conventional UDS 28 . In a prospective study of 106 women with UUI, involuntary detrusor activity was identified in 32 patients using conventional UDS and in 70 patients using AUM (patients underwent both procedures in a randomized crossover design) 12 .…”
Section: Ambulatory Urodynamic Monitoringmentioning
confidence: 99%